Burden of Breast Cancer in the Arab World: Findings from Global Burden of Disease, 2016 - M. Jawad Hashim; Fatima A. Al-Shamsi; Noura A. Al-Marzooqi; Sarah S. Al-Qasemi; Ali H. Mokdad; Gulfaraz Khan (Springer, 2018)
Epidemiology of breast cancer in the Arab region is understudied as compared with Western countries. We aimed to examine breast cancer epidemiology in Arab countries from 1990 to 2016. We analyzed the Global Burden of Disease, 2016 data for breast cancer among women in 22 Arab countries. Epidemiological measures including incidence, mortality, and disability adjusted life years (DALYs) were analyzed for breast cancer in women from 1990 to 2016. We also measured the burden of breast cancer stratified by the sociodemographic index (SDI). Our analysis indicates that the incidence of breast cancer in Arab women has risen over the past 26 years, but is still lower than global averages. In 2016, there were 45,980 new cases (28/100,000) and 20,063 deaths (11/100,000) in the region. The burden of breast cancer as estimated by DALYs was also lower than the global rates and tended to increase with increasing SDI. Although some studies have reported that Arab women present with breast cancer at a younger age, our analysis of age-specific rates, indicates that this is not statistically significant. Our findings indicate that a comprehensive plan to improve public awareness, screening, diagnosis, and treatment is required to reduce the growing burden of breast cancer in the Arab world.